2010
DOI: 10.5194/hess-14-2207-2010
|View full text |Cite
|
Sign up to set email alerts
|

Surface and subsurface flow effect on permanent gully formation and upland erosion near Lake Tana in the northern highlands of Ethiopia

Abstract: Abstract. Gully formation in the Ethiopian Highlands has been identified as a major source of sediment in water bodies, and results in sever land degradation. Loss of soil from gully erosion reduces agricultural productivity and grazing land availability, and is one of the major causes of reservoir siltation in the Nile Basin. This study was conducted in the 523 ha Debre-Mawi watershed south of Bahir Dar, Ethiopia, where gullies are actively forming in the landscape. Historic gully development in a section of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 22 publications
5
139
0
Order By: Relevance
“…Zegeye et al (2010) and Tilahun et al (2015) showed that rill formation stopped in August, and soil loss was greatly decreased from the uplands. The correlation of soil loss with plant cover was very weak (Tebebu et al, 2010) excluding plant cover as the cause for the decrease. Assuming that all sediment loss is originating from the agricultural areas the sediment concentrations can be scaled as the quotient of the observed concentration and the fraction of agricultural land in the watershed.…”
Section: Hydrological Similarity Of Watershedsmentioning
confidence: 94%
See 4 more Smart Citations
“…Zegeye et al (2010) and Tilahun et al (2015) showed that rill formation stopped in August, and soil loss was greatly decreased from the uplands. The correlation of soil loss with plant cover was very weak (Tebebu et al, 2010) excluding plant cover as the cause for the decrease. Assuming that all sediment loss is originating from the agricultural areas the sediment concentrations can be scaled as the quotient of the observed concentration and the fraction of agricultural land in the watershed.…”
Section: Hydrological Similarity Of Watershedsmentioning
confidence: 94%
“…Precipitation, discharge and storm event sediment yields are available from 1988-1994, 1996-2004, and 2008 (Table 1). 16901984-1993-2013Liu et al, 2008Guzman et al, 2013;Tilahun et al, 2013a,b;Elkamil, 2014;Tebebu et al, 2014;Bayabil et al, 2015 Maybar 113 Phaeozems and Phaeozems associated to Lithosols 12101988-19941996-2004Liu et al, 2008Bayabil, 2009;Bayabil et al, 2010;Guzman et al, 2013 Andit Tid 481 Andosols and Regosols 15001986-19921994-2001Liu et al, 2008Engda, 2009;Guzman et al, 2013;Tilahun et al, 2013b Debre Mewi 95 Nitosols and Vertisols 1240-2014Abiy, 2009Tebebu, 2009;Tebebu et al, 2010;Zegeye et al, 2010;Tilahun, 2012;Langendoen et al, 2013;Dagnew et al, 2014;Tebebu et al, 2014;Zegeye et al, 2014;Dagnew et al, 2015;Tilahun et al, 2015 The Andit Tid watershed, situated 180 km northeast of Addis Ababa at 39 • 43 ′ E and 9 • 48 ′ N, covers 481 ha ( …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations